Respuesta :

[tex]x = \sqrt{6x - 9} \\[/tex]

Square both sides.

[tex]x^2 = 6x - 9[/tex]

Move all terms to one side.

[tex]x^2 - 6x + 9 = 0[/tex]

Simplify using AC method.

[tex]x^2 - 6x + 9 = (x - 3)(x - 3)[/tex]

x = 3


Answer:

x = 3

Step-by-step explanation:

First, get rid of the square root by squaring both sides of the equation.

x^2 = √(6x - 9)^2

Simplify.

x^2 = 6x - 9

Move 6x-9 to the other side of the equation and set it equal to zero.

x^2 - 6x + 9 = 0

Factor.

(x - 3)(x - 3) = 0

x = 3